Tribological and corrosion behaviors of carburized AISI 4340 steel - Atcharawadi Thong-On (2018)
© 2016 The Japan Society of Applied Physics. AISI 4340 steel is widely used in automotive and aircraft industries as gear components. In such applications, surface hardening processes such as carburizing are required in order to improve the life time of the components. There are many studies showing the tribological behavior of the carburized steel, but the corrosion behavior has not yet been clarified. This paper reports on both tribological and corrosion behaviors of the carburized AISI 4340 steel. Factor associated with carburizing, such as the quantities of deposited carbon, dissolved carbon, and formed Cr23C6 and Fe3C, affect the tribological and corrosion behaviors of the steel by improving hardness, friction, lubrication, and wear resistance; but corrosion resistance is reduced. The dissolved carbon affects the formation of the oxide layer of the carburized steel, by obstructing the continuous oxide layer formation and by decreasing the chromium content of the steel, leading to the decrease in the corrosion resistance of the steel.